The Role of Sport in the Process of Negotiating Identity: Dealing with the Stigma of Disability by People with Acquired Bodily Dysfunctions - Niedbalski, Jakub (Qualitative Sociology Review, 2020)
This paper is intended to present the role of sport in the lives of people with physical disabilities and to determine how practicing sports changes the way a person with a physical disability sees themselves. The paper reflects the experiences of people who started practicing sports, which allowed them to adopt an alternative perspective of their bodies and thus pushed them to negotiate their identities. Using the concept of Goffmanian stigma, I point to the sports activities’ usefulness in understanding the management of stigma by those dealing with a physical disability.Taking into account the above theoretical references, in the research, which constitutes a foundation of this paper, I refer to the subjective perspectives of the researched individuals, rendering their points of view, and, based on that, construct and offer theoretical generalizations. Therefore, the research materials employed in this study are constituted by the personal experiences of people with physical disabilities who practice sports. All data have been gathered by conducting unstructured interviews with such people. The research materials were analyzed and interpreted following the procedures of grounded theory methodology.